UAV Orthophoto Poster Kg Morten, Melaka - Abdullah, Alias; Ibrahim, Illyani; Ibrahim, Mansor; Hj. Mohd. Noor, Norzailawati; Harun, Nor Zalina; Abdul Latip, Nurul Syala; Abdullah, Ahmad Afiq Aiman; N Murtaza, Fatin Farhana (2020)
UAV Orthophoto of Kg Morten with scale 1:4000